1999
DOI: 10.1016/s1098-612x(99)90006-2
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Mycobacterium Genavense Infection in a FIV-Positive Cat

Abstract: An 8-year-old FIV-positive Australian cat was presented with coughing, periocular alopecia, pyrexia and inappetence. Skin scrapings demonstrated Demodex cati mites. Antibiotics were administered and it was treated successfully for periocular demodectic mange, but the cat continued to exhibit respiratory signs and lose weight. Further investigation revealed an ascarid infection and active chronic inflammation of undetected cause affecting the lower airways. Repetitive treatment with pyrantel failed to eradicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 29 publications
(38 reference statements)
0
47
0
1
Order By: Relevance
“…A M. genavense infection is described in the literature as a disseminated mycobacteriosis in humans and animals with granulomatous inflammation of several organs (intestine, liver, spleen, lymph nodes, bone marrow, skin, kidneys, lungs, and brain). 2,3,[7][8][9][10][11]13,14,[16][17][18] However, the lungs were the only affected organs in our case, whereas the abdominal organs and lymphatic tissues were without pathologic findings, consistent with M. genavense infection. Besides disseminated forms of nontuberculous mycobacterial infections, exclusively chronic pulmonary infections are described, commonly associated with M. kansasii or M. xenopi.…”
mentioning
confidence: 86%
“…A M. genavense infection is described in the literature as a disseminated mycobacteriosis in humans and animals with granulomatous inflammation of several organs (intestine, liver, spleen, lymph nodes, bone marrow, skin, kidneys, lungs, and brain). 2,3,[7][8][9][10][11]13,14,[16][17][18] However, the lungs were the only affected organs in our case, whereas the abdominal organs and lymphatic tissues were without pathologic findings, consistent with M. genavense infection. Besides disseminated forms of nontuberculous mycobacterial infections, exclusively chronic pulmonary infections are described, commonly associated with M. kansasii or M. xenopi.…”
mentioning
confidence: 86%
“…genavense is the most common mycobacterial infection in birds (106), which to date are the only identified potential reservoir. Les frequent are infections in other animals, including a disseminated infection in an immunodeficient cat (67).…”
Section: Genavensementioning
confidence: 99%
“…In contrast, the present study and a number of other investigations [17,22,43] found the prevalence of these retroviral infections was comparable to reference populations of non-descript 'sick' cats. Although there are a few reports of sequential opportunistic infections in FIVpositive cats [32,46] no case Á/control studies have provided convincing evidence that any given infectious disease is seen at increase frequency in cats with chronic FIV infection. Likewise, CD4 counts in FIV-positive cats with cryptococcosis were comparable to CD4 counts in FIV-negative cats with cryptococcosis [47].…”
Section: Feline Cryptococcosismentioning
confidence: 99%